2022
DOI: 10.1177/21677026211068873
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchical Taxonomy of Psychopathology (HiTOP) Is Not an Improvement Over the DSM

Abstract: In their response to our article (both in this issue), DeYoung and colleagues did not sufficiently address three fundamental flaws with the Hierarchical Taxonomy of Psychopathology (HiTOP). First, HiTOP was created using a simple-structure factor-analytic approach, which does not adequately represent the dimensional space of the symptoms of psychopathology. Consequently, HiTOP is not the empirical structure of psychopathology. Second, factor analysis and dimensional ratings do not fix the problems inherent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For example, bifactor models of general psychopathology are often favored over unidimensional and other correlated factor models because bifactor models yield the best model fit. However, studies have shown that bifactor models fit well even when there are spurious reasons for it, e.g., random patterns and not valid responses, suggesting that both signal and noise are overfitting the data (Fried, 2020;Haeffel et al, 2022;Reise et al, 2016;. In light of overreliance on goodness of fit and other flaws in bifactor modeling approaches, Bonifay and colleagues (2017) suggested that other bifactor statistics, such as explained common variance, may prove more useful than goodness of fit in evaluating indices of general factor modeling.…”
Section: Criticisms Of General Psychopathology Modelingmentioning
confidence: 99%
“…For example, bifactor models of general psychopathology are often favored over unidimensional and other correlated factor models because bifactor models yield the best model fit. However, studies have shown that bifactor models fit well even when there are spurious reasons for it, e.g., random patterns and not valid responses, suggesting that both signal and noise are overfitting the data (Fried, 2020;Haeffel et al, 2022;Reise et al, 2016;. In light of overreliance on goodness of fit and other flaws in bifactor modeling approaches, Bonifay and colleagues (2017) suggested that other bifactor statistics, such as explained common variance, may prove more useful than goodness of fit in evaluating indices of general factor modeling.…”
Section: Criticisms Of General Psychopathology Modelingmentioning
confidence: 99%
“…However, these new models, although highly inspiring to overcome classic categorical approach, are currently hardly implemented in common clinical practice ( 32 , 38 ), where categorical approach remains the most used, even though work groups are working on implementing dimensional approaches ( 32 , 39 ). Finally, these models are also not free of criticisms, either on their overall utility [e.g., for HiTOP ( 40 )] or on their representativeness of the clinical complexity of patients [e.g., for AMPD/ICD-11 ( 41 )].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypes that target intraindividual heterogeneity may have clinical utility. Whereas contemporary literature on depression has promoted dimensional conceptualizations of psychopathology (Forbes et al, 2016), sophisticated categorical classification systems may remain efficient for practitioners' decision making (Haeffel et al, 2022). For example, intraindividual phenotypes can represent clinically relevant states that can signal when a particular intervention may be especially helpful for a particular individual.…”
Section: Introductionmentioning
confidence: 99%